Linguopragmatic Analysis Of Neologisms Functioning In The Discourse Of Mass Media (Diversity Research: Journal of Analysis and Trends, 2026)
This article examines neologisms in the context of media discourse. Neologisms in the media are of particular interest to researchers, as it is in this context that words must be striking and memorable for the audience. The media act as the primary channel for the dissemination and popularization of these neologisms. It is emphasized that evaluative words reveal linguistic identity in the lexical-semantic system